History and Debut of the Ski-Mountaineering - Martinescu-Bădălan Fabiana; Stănciulescu Robert (Scientific Bulletin, 2019)
Since ancient times, skiing has been a way of moving, born out of a spirit of survival. The usefulness of this means of transportation has undergone numerous transformations with implications in terms of utility-applied aspect as well as in the area of sports and recreation. Military Physical Education, as a component of military training, includes utility-applied skiing, focusing in particular on cross-country skiing and ski touring. The modern battlefield requires military training in increasingly complex and new areas in this century, with a focus on the formation of well-trained and multispecialized armies of professionals, to the detriment of mass armies. Ski-mountaineering has increasingly evolved over the last few years, due to the possibility of reaching relatively fast on the ridge tips and lowering even faster, eliminating the barriers imposed by the relief. As the name calls it, it combines the techniques and procedures of skiing with mountaineering.